2014
DOI: 10.1111/jocn.12597
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceived and actual caregiving roles: identifying factors that can contribute to job satisfaction

Abstract: It is important to identify factors that could explain resilience to compassion fatigue because compassion fatigue has negative consequences not only for nurses themselves but for the patients in their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 19 publications
2
51
1
1
Order By: Relevance
“…Previous studies have also reported discrepancies between management expectations and the care given by nurses. Nurses have previously reported that they do not receive sufficient support from the management and that their opinions are not valued (Kaddourah et al., ; Morrison & Korol, ; Pin‐Pin Choi, Cheung, & Mei‐Che Pang, ). Moreover, RNs in this study reported that, at times, they are dissatisfied with the chances for career development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported discrepancies between management expectations and the care given by nurses. Nurses have previously reported that they do not receive sufficient support from the management and that their opinions are not valued (Kaddourah et al., ; Morrison & Korol, ; Pin‐Pin Choi, Cheung, & Mei‐Che Pang, ). Moreover, RNs in this study reported that, at times, they are dissatisfied with the chances for career development.…”
Section: Discussionmentioning
confidence: 99%
“…These concepts include: missing nursing care, perceptions of staff, monitoring, patient advocacy, role conflict with management, patient death and suffering, violence, dealing with patients' families, feelings of powerlessness, physical distress, and moral conflict. [23][24][25] Sources of coping with stress were also explored including: caring, helping families, relationships with colleagues, and job satisfaction.…”
Section: Affectivementioning
confidence: 99%
“…The purpose of Morrison and Korol's study was to compare the type of care nurses expect to provide, to identify when and whether disconnect in expectations led to compassion fatigue. The authors proposed a job satisfaction model where upon perceiving control and optimal challenge from a work environment, nurses derive reward, feel energetic and these feelings strengthen commitment to their job (Morrison & Korol, 2014). In contrast, the authors describe compassion fatigue, empathetically engaging with patients and integrating the emotions of fear, grief and loss, when nurses experience time/resource constraints and role conflict.…”
Section: Discussionmentioning
confidence: 98%
“…Nurses frequently focused on caring for patients, the happiness and satisfaction which promoted their emotional wellbeing. Morrison and Korol (2014) investigated actual and perceived caring roles of nurses in a grounded theory study of nine Canadian nurses. Overwhelmingly, nurses were focused on providing care that was "in the patients' best interest".…”
Section: Discussionmentioning
confidence: 99%